MicroRNA-10b overexpression promotes non-small cell lung cancer cell proliferation and invasion - Liu, Yi (BioMed Central, 2013)
BACKGROUND: miRNAs are a class of small non-coding RNA molecules that play an important role in the pathogenesis of human diseases through negative regulation of gene expression. Although miRNA-10b (miR-10b) has been implicated in other tumors, its role in non-small cell lung cancer (NSCLC) is still unknown. The aim of the present study was to investigate the role of miR-10b in NSCLC. METHODS: Expression of miR-10b was analyzed in NSCLC cell line A549 by qRT-PCR. Cell viability was evaluated using Cell Counting Kit (CCK)-8. Cell migration and invasion were evaluated by wound healing assay and transwell assays. Cell cycle and apoptosis analyses were performed. Western blotting was used to predicate the target of miR-10b. RESULTS: The A549 cell line transfected with the miR-10b exhibited significantly increased proliferation, migration, and invasion capacities when compared with the control cells (P < 0.05). Krüppel-like factor 4 (KLF4) may be indirectly targeted by miR-10b during the proliferation increasing of A549 cells. CONCLUSION: In this study, we found that miR-10b is a tumor enhancer in NSCLC. Thus, miR-10b may represent a potential therapeutic target for NSCLC intervention.